Decomposition Kinetics Of Flash Smelting Flue Dust Sulphates (EPD Congress 2006) - Elli Nurminen (The Minerals, Metals and Materials Society, 2006)
In this work the thermodynamics of the metallic sulphate decomposition reactions were studied through thermodynamical calculations and thermogravimetric methods. The decomposition temperatures and mechanisms were determined for cupric sulphate, ferric sulphate and also for industrial flue dust from a copper flash smelting process. The aim was to determine the thermodynamic conditions for sulphate decomposition and to estimate whether the reactions are kinetically likely to take place in the flash smelting process heat recovery equipment. The information is essential in CFD-modelling of the reactions taking place in the boiler and for optimising the process.